Arbitration under Saudi legal system and Malaysian law - Halawani, Mohammad Khaled; Omar, Muhammad Naim (The Mattingley Publishing Co Inc, 2020)
Arbitration is an expression of the desire of the parties to a dispute by submitting the subject of their dispute to arbitration through a special court or tribunal, and choose an applicable law to conduct the dispute proceedings. Arbitration saves the time and effort of the parties since it is fast, and also confidential in proceedings. This research reveals the nature of the arbitration proceedings under the Saudi legal system and Malaysian law. It also highlights both the Saudi legal system and the Malaysian law in procedural terms, with clarification of the parameters of the legal procedures for arbitration in the Saudi legal system and Malaysian law, and the similarities and differences in procedural arbitration. It also investigates the analytical, descriptive approach to clarify the procedural steps of arbitration in Saudi and Malaysian law, inductive approach, comparative approach to identifying similarities and differences between Saudi and Malaysian law, as well as the fundamental differences between regimes.